Abracadabra! Magic with Mouse and Mole - Yee, Wong Herbert (Houghton Mifflin, 2007)
Mole is mad about magic until he takes his friend Mouse to a show that turns out to be all tricks, but then Mouse conjures up a special night program to show him the enchantment found in nature.